(untitled) (Indian Journal of Child Health, 2014)
Mongolian spots are congenital hyperpigmented macules of varying size and shape and are usually grayish in color. They occur commonly in the sacrococcygeal area, followed by the gluteal and lumbar areas. We report a Chinese infant with a Mongolian spot in the frontal area; the occurrence of a Mongolian spot in this location is considered exceptional. Awareness of such an occurrence is important, and hence that a false accusation of child abuse is not made.